2021
DOI: 10.1101/2021.06.13.448152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-nucleus transcriptomes reveal functional and evolutionary properties of cell types in the Drosophila accessory gland

Abstract: Many traits responsible for male reproduction evolve quickly, including gene expression phenotypes in germline and somatic male reproductive tissues. Rapid male evolution in polyandrous species is thought to be driven by competition among males for fertilizations and conflicts between male and female fitness interests that manifest in post-copulatory phenotypes. In Drosophila, seminal fluid proteins secreted by three major cell types of the male accessory gland and ejaculatory duct are required for female sper… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 116 publications
(172 reference statements)
0
4
0
Order By: Relevance
“…2006) or the expression of different homologues in the AG of different species (Ahmed-Braima et al 2017; Cridland et al . 2020, 2022; Hurtado et al . 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…2006) or the expression of different homologues in the AG of different species (Ahmed-Braima et al 2017; Cridland et al . 2020, 2022; Hurtado et al . 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recent RNA-seq analysis of the SC has revealed that its transcriptome is distinct from that of the main cells and also evolves in a distinct manner (Immarigeon et al . 2021, Majane et al . 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations